A Dynamic Theory of Regulatory Capture - Alessandro De Chiara; Marco Schwarz (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Firms often try to influence individuals that, like regulators, are tasked with advising or deciding on behalf of a third party. In a dynamic regulatory setting, we show that a firm may prefer to capture regulators through the promise of a lucrative future job opportunity (i.e., the revolving-door channel) than through a hidden payment (i.e., a bribe). This is because the revolving door publicly signals the firm's eagerness and commitment to rewarding lenient regulators, which facilitates collusive equilibria. We find that opening the revolving door conditional on the regulator's report is usually more efficient than a blanket ban on post-agency employment and may increase social welfare. This insight extends to a variety of applications and can also be used to determine the optimal length of cooling-off periods.
Keywords: D73; D86; H11; J45; L51; 330; collusion; cooling-off periods; corruption; dynamic games; experts; regulation; regulatory capture; revolving door